Realtime Object’s Size Measurement from Distance using OpenCV and LiDAR - et. al., Dr. Bhavesh R. Patel, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this paper, we are proposing a method to estimating the object’s size from distance using computer vision and LiDAR Sensor. The paper contains steps to gain the solution, training dataset with formulas, and its limitations. Proposed methods are to be implemented in robotics engineering, self-driving drone, car, and many more. This proposed algorithm aims to measure the size of an object from distance using the LiDAR sensor, Camera, and OpenCV Algorithm. This paper also includes a brief introduction of OpenCV, LiDAR Sensor, Realtime Object Detection methods.